Effect of Slow Deep Breathing on Muscle Pain Reduction among Adults with Myalgia: A Quasi-Experimental Study - Rustini, Sri Anik; Taukhid, Taukhid; Hasanah, Uswatun; Sari, Ninik Ambar; Widyastuti, Merina (Journal of Applied Nursing and Health, 2026)
Background: Relaxation techniques and slow deep breathing are known to activate the parasympathetic nervous system, making them an integral non-pharmacological intervention for musculoskeletal pain management. However, evidence regarding the effectiveness of slow deep breathing interventions in reducing muscle pain in adults with myalgia, particularly in primary care settings, is limited. This study aimed to examine the effect of slow deep breathing on reducing muscle pain in adults with myalgia. Methods: This study used a quasi-experimental pre-test-post-test control group design following TREND guidelines. Total sampling was used to recruit 36 myalgia patients at the Peneleh Community Health Center, Surabaya, who were divided into an intervention group (n = 18) and a control group (n = 18). Participants aged 17–65 years with pain intensity ≥3 on the Numeric Rating Scale (NRS) were included. The intervention group received slow deep breathing exercises for 15 minutes twice daily for five days, while the control group received standard care. Muscle pain intensity measured using the NRS was the outcome variable. Data were analyzed using the Wilcoxon Signed Rank Test due to non-normal distribution and the Mann–Whitney U test, with p < 0.05 considered statistically significant. Results: Muscle pain intensity in the intervention group significantly decreased from 4.33 ± 0.84 to 2.50 ± 1.15, showing a mean reduction of 1.83 points (Wilcoxon Signed Rank Test, p < 0.001). The control group showed no significant change (from 4.22 ± 0.81 to 4.00 ± 0.80; mean reduction = 0.22; p = 0.102). Posttest comparison demonstrated significantly lower pain intensity in the intervention group than in the control group (mean rank 24.67 vs 12.33; Mann–Whitney U = 51.0, p < 0.001). Conclusion: Slow deep breathing for five days significantly reduced muscle pain intensity in patients with myalgia compared to standard care, suggesting it is an effective non-pharmacological intervention for pain management in primary care settings.